Distribution and genetic features of the causative agent of Alaria alata in wild carnivores of the steppe and forest-steppe zones of Kazakhstan - Smagulova, A.M.; Uakhit , R.S.; Lider L.А.; Lyalchenko А.S.; Kiyan , V.S. (Eurasian Journal of Applied Biotechnology, 2022)
This article presents data on the study of the Alaria spp. pathogen isolated from wild carnivores (corsacs, foxes, wolves) caught in the territory of Karaganda, Kostanay, Akmola, and East Kazakhstan regions in the period from 2019 to 2022. As a result of the autopsy of wild animals, a collection of Alaria spp. was collected, the intensity of invasion varied from 1 to 1489 samples/animal, and the prevalence of invasion ranged from 10 to 36.11%. The primary taxonomic affiliation of the pathogen was carried out using determinants. Genetic identification was carried out by amplification of a section of the internal transcribed spacer 2 (ITS2) marker gene. The resulting 557 bp amplicons. sequenced using the Sanger method. The nucleotide sequences were deposited in the international GenBank database under accession numbers: from the fox - OM630451, ON248128, ON248130, from the corsac - OM630460, ON248043, ON248044, ON248045, from the wolf - ON358106. Bioinformatics analysis to build a phylogeny showed that the samples of Alaria alata studied by us were combined into a separate cluster by identity, which ranged from 90-98%.